Ragtime - Doctorow, E. L., 1931- (New York : Random House, 1975)
Set in America in the early 1900s, this is the story of three remarkable families lives' become entwined with Henry Ford, Harry Houdini, J.P. Morgan, Theodore Dreiser, Sigmund Freud, and Emiliano Zapata at the turn of the century.
930
Keywords: Historical fiction; United States -- History -- 1901-1909 -- Fiction; New York (State) -- History -- 1865- -- Fiction